2010
DOI: 10.1530/eje-10-0640
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and novel biomarkers of treatment outcome in patients with acromegaly: discordant results after somatostatin analog treatment compared with surgery

Abstract: Context: Control of disease activity in acromegaly is critical, but the biochemical definitions remain controversial. Objective: To compare traditional and novel biomarkers and health status in patients with acromegaly treated with either surgery alone or somatostatin analog (SA). Design and methods: Sixty-three patients in long-term remission based on normalized total IGF1 levels after surgery alone (nZ36) or SA (nZ27) were studied in a cross-sectional manner. The groups were comparable at diagnosis regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 51 publications
(57 reference statements)
6
23
0
3
Order By: Relevance
“…1a). This is further supported by a recent report by Rubeck et al (43). They compared traditional and novel biomarkers and health status in patients with acromegaly treated with either surgery alone or SMSA.…”
Section: How Somatostatin Analogs Worksupporting
confidence: 64%
See 1 more Smart Citation
“…1a). This is further supported by a recent report by Rubeck et al (43). They compared traditional and novel biomarkers and health status in patients with acromegaly treated with either surgery alone or SMSA.…”
Section: How Somatostatin Analogs Worksupporting
confidence: 64%
“…They reported that despite similar and normalized IGF1 levels, SMSA treatment compared with surgery alone was associated with less suppressed GH levels and less symptom relief. They concluded that this discordance may be due to specific suppression of hepatic IGF1 production by SMSA (43).…”
Section: How Somatostatin Analogs Workmentioning
confidence: 99%
“…It is postulated by Neggers et al (37) that long-acting SSTA normalize serum IGF1 levels in certain patients in the presence of elevated GH actions in extrahepatic tissues. Also, Rubeck et al (38) compared traditional and novel biomarkers and health status in patients with acromegaly treated with either surgery alone or SSTA. These authors concluded that despite similar and normalized IGF1 levels, SSTA treatment compared with surgery alone was associated with less suppressed GH levels and less symptom relief.…”
Section: Discussionmentioning
confidence: 99%
“…Rubeck et al hanno valutato, in acromegalici trattati soltanto chirurgicamente o con LA-SMSA, differenti biomarcatori e lo stato di salute globale [11]. Le IGF-I totali e biologicamente attive erano simili; nel gruppo trattato con LA-SMSA i livelli di GH in risposta al carico di glucosio risultavano più elevati rispetto ai pazienti sottoposti a chirurgia mentre lo stato di salute specifico della malattia risultava migliore nei pazienti operati [11].…”
Section: Come Agiscono Gli Analoghi Della Somatostatinaunclassified